CHALLENGES AND GUIDELINES FOR INTEGRATING SUSTAINABLE PRACTICES IN THE ACTIVITIES OF CONSTRUCTION COMPANIES - Luchkov Кiril (E-Journal VFU, 2025)
The study identifies the main challenges that hinder the implementation of sustainable practices in the activities of construction companies. The most significant of these are financial constraints, lack of expertise, regulatory uncertainty, and low public awareness. Based on the analysis, guidelines for overcoming these challenges are formulated. They include the use of green financing, investment in training and innovation, improved coordination between participants in the construction process, and other similar measures.